Comparing respirator laboratory protection factors measured with novel personal instruments to those from the PortaCount. Issue 2 (1st February 2021) - Persing, Allison J.; Sietsema, Margaret; Farmer, K. R.; Peters, Thomas M.
Abstract: A quantitative fit test is performed using a benchtop instrument (e.g., TSI PortaCount) to assess the fit factor provided by a respirator when assigned to a worker. There are no wearable instruments on the market to measure protection factors while the respirator is in use. The aim of this study is to evaluate two new, wearable, quantitative instruments—a dual-channel optical particle counter (DC OPC) and a dual-channel condensation particle counter (DC CPC)—that would enable in-situ, real-time measurement of respirator workplace protection factor. Respirator laboratory protection factors measured by the new instruments were compared to those measured with the TSI PortaCount on one test subject for three test aerosols (sodium chloride, incense, ambient) at target laboratory protection factors of 100, 300, and 1, 000 for sodium chloride and ambient, and 75 and 500 for incense. Three replicates were performed for each test condition. Data were analyzed with a two-sided paired t-test at a significance level of 0.05. Laboratory protection factors measured with the DC CPC agree with those measured with the PortaCount whereas those from the DC OPC generally do not. Mean laboratory protection factors derived from the DC CPC are only statistically significantly different for mean values of a laboratory protection factor at ambient conditions for a target laboratory protection factor of 300 ( p = 0.02) and for incense at a target laboratory protection factor of 75 ( p = 0.03). Although statistically significant, the difference in laboratory protection factors derived from the DC CPC are not substantial in practice and may be explained by systematic uncertainty. In contrast, the DC OPC reports substantially larger mean laboratory protection factors, differing by about half an order of magnitude in extreme cases, and statistically significantly different mean laboratory protection factors for the sodium chloride aerosol for target laboratory protection factors of 100 and 300 ( p = 0.01 and p = 0.01).